Working relationship between local fishermen and migrant fishermen in Palu Bay - Anriani, Haslinda Baji; Harifuddin, Harifuddin; Abdullah, Suparman (ETNOSIA : Jurnal Etnografi Indonesia, 2022)
This study aims to analyze: (1) Patterns of cooperation and profit sharing as a form of reciprocal relations between local fishermen and migrant fishermen, (2) The level of welfare of local fishermen as a consequence of these reciprocal relations. To answer this question, a study was held in Lere Village, Palu Bay. This research is qualitative with sampling techniques using Purposive sampling. Data collection was carried out with in-depth interviews and engaged observations and literature studies. Data analysis uses a three-step technique, namely data reduction, data categorization, conclusions. The results of this study are: (1) Patterns of cooperation and profit sharing as a form of reciprocal relations between local fishermen and migrant fishermen include: labor deployment, profit sharing rules, fish marketing with pattern rules. (2) The level of welfare of local fishermen as a consequence of mutual relations before cooperating and after cooperation includes: Ownership of more modern means of production, increased income, better home conditions, more varied ownership of household appliances, and ownership of more transportation facilities than before. The conclusion of this study is that the presence of migrant fishermen is very large for improving the welfare of local traditional fishermen in Palu bay